Village production of West African Dwarf goats and sheep in Nigeria - Sumberg, J.E.; Mack, S.D. (Springer, 1985)
Reports results from a 41 month study of West African Dwarf goats and sheep under village conditions in South-West Nigeria. Presents data on distribution by age and sex; reasons for animals leaving the survey; reproductive performance; litter size; weight at different ages and probability survival of kids and lambs.